Upaya Mengembangkan Kemampuan Kognitif Anak dalam Mengenal Lambang Bilangan 1-10 Menggunakan Media Loose Part Melalui Kegiatan Bermain Variatif pada Anak Kelompok A TK Teratai Birayang - Nisa, Khairatun; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
The background of this research is that children's ability to recognize number symbols 1-10 is still low due to the lack of varied teacher and media approaches. If this problem is not solved, it will have a low impact on knowing numbers and children will experience difficulties in their cognitive aspects. The purpose of this study was to find out the teacher's activities, children's activities, and their developmental achievements in the cognitive aspect in recognizing the number symbols 1-10 through various play activities using loose part media as a model in learning. This research was conducted using a qualitative research approach in the type of Classroom Action Research (CAR) with research subjects of class A children at Teratai Birayang Kindergarten, totaling 12 children. The type of research data is qualitative research where the data collection method is obtained from observation sheets of teacher and child activities while quantitative research methods for collecting data are obtained from children's learning outcomes sheets. Data analysis was descriptive qualitative and cross-tabulation with indicators of teacher activity achieving a score of ≥ 27 in the "Very Good" category, children's classical activity with a score of ≥ 76 in the "Very Active" category, and the child's development results at least got more than or equal to three stars. From the results of the study it was concluded that using loose part media through these varied playing activities can develop children's ability to recognize the symbols of numbers 1-10. For school principals it is suggested to be able to provide guidance to all teachers, for teachers it is suggested to be able to practice the combination of models that researchers do at school and for other researchers it is suggested to be able to develop a combination of these models.